Viewers and Identity Consciousness: The Analysis of the Responses of Green Street’s Viewers - Ayuningtyas, Paramita (Bina Nusantara University, 2009)
English and Indonesian have similar rules in the placement of head noun in adjective clause, that is head noun precedes the clause. However, in English it is possible to reduce the clause while in Indonesian it is not possible to do it. This difference causes difficulty for students learning English especially those whose language background is different. Binus University students come from different provinces around Indonesia and thus they have different language backgrounds. The research declares the difference of this background in identifying reduced clause. They are categorized into monolinguals if they only speak Indonesian at home and bilinguals if they speak both Indonesian and their ethnic languages. The purpose of this study is to find out whether bilinguals perform better than monolinguals, or vice versa, in processing reduced clause sentences. Â